Vocomotor and social brain networks work together to express social traits in voices - Guldner, Stella; Nees, Frauke; McGettigan, Carolyn (Cerebral cortex, 2020)
Voice modulation is important when navigating social interactions—tone of voice in a business negotiation is very different from that used to comfort an upset child. While voluntary vocal behavior relies on a cortical vocomotor network, social voice modulation may require additional social cognitive processing. Using functional magnetic resonance imaging, we investigated the neural basis for social vocal control and whether it involves an interplay of vocal control and social processing networks. Twenty-four healthy adult participants modulated their voice to express social traits along the dimensions of the social trait space (affiliation and competence) or to express body size (control for vocal flexibility). Naïve listener ratings showed that vocal modulations were effective in evoking social trait ratings along the two primary dimensions of the social trait space. Whereas basic vocal modulation engaged the vocomotor network, social voice modulation specifically engaged social processing regions including the medial prefrontal cortex, superior temporal sulcus, and precuneus. Moreover, these regions showed task-relevant modulations in functional connectivity to the left inferior frontal gyrus, a core vocomotor control network area. These findings highlight the impact of the integration of vocal motor control and social information processing for socially meaningful voice modulation.